Auditory connections and functions of prefrontal cortex - Plakke, Bethany; Romanski, Lizabeth M. (Frontiers in Neuroscience, 2014)
The functional auditory system extends from the ears to the frontal lobes with successively more complex functions occurring as one ascends the hierarchy of the nervous system. Several areas of the frontal lobe receive afferents from both early and late auditory processing regions within the temporal lobe. Afferents from the early part of the cortical auditory system, the auditory belt cortex, which are presumed to carry information regarding auditory features of sounds, project to only a few prefrontal regions and are most dense in the ventrolateral prefrontal cortex (VLPFC). In contrast, projections from the parabelt and the rostral superior temporal gyrus (STG) most likely convey more complex information and target a larger, widespread region of the prefrontal cortex. Neuronal responses reflect these anatomical projections as some prefrontal neurons exhibit responses to features in acoustic stimuli, while other neurons display task-related responses. For example, recording studies in non-human primates indicate that VLPFC is responsive to complex sounds including vocalizations and that VLPFC neurons in area 12/47 respond to sounds with similar acoustic morphology. In contrast, neuronal responses during auditory working memory involve a wider region of the prefrontal cortex. In humans, the frontal lobe is involved in auditory detection, discrimination, and working memory. Past research suggests that dorsal and ventral subregions of the prefrontal cortex process different types of information with dorsal cortex processing spatial/visual information and ventral cortex processing non-spatial/auditory information. While this is apparent in the non-human primate and in some neuroimaging studies, most research in humans indicates that specific task conditions, stimuli or previous experience may bias the recruitment of specific prefrontal regions, suggesting a more flexible role for the frontal lobe during auditory cognition.